Rabies Virus Transmission in Solid Organ Transplantation, China, 2015–2016 - Shuilian Chen; Heng Zhang; Meiling Luo; Jingfang Chen; Dong Yao; Faming Chen; Ruchun Liu; Tianmu Chen (Emerging Infectious Diseases, 2017)
We report rabies virus transmission among solid organ transplantation recipients in Changsha, China, in 2016. Two recipients were confirmed to have rabies and died. Our findings suggest that more attention should be paid to the possibility of rabies virus transmission through organ transplantation for clinical and public health reasons.